The handbook for enhancing professional practice : using the framework for teaching in your school - Danielson, Charlotte (Association for Supervision and Curriculum Development, 2008)
This book focuses on building the capacity of teachers, supporting teachers to help them reach their potential, and making the best use of teachers' individual and collective contributions to school improvement efforts.